Expression, purification and crystallization of Asrij, A novel scaffold transmembrane protein - Motiwala, Zenia; Darne, Priti; Prabhune, Asmita; Inamdar, Maneesha S.; Kulkarni, Kiran (Journal of Membrane Biology, 2021)
Asrij/OCIAD1 is a scaffold transmembrane protein belonging to the Ovarian Carcinoma Immunoreactive Antigen Domain containing protein family. In Drosophila and mouse models, Asrij localizes at the endosomal and mitochondrial membrane and is shown to regulate the stemness of hematopoietic stem cells. Interaction of Asrij with ADP Ribosylation Factor 1 (Arf1) is shown to be crucial for hematopoietic niche function and prohemocyte maintenance. Here, we report the heterologous expression, standardization of detergents and purification methodologies for crystallization of Asrij/OCIAD1. To probe the activity of bacterially expressed Asrij, we developed a protein complementation assay and conclusively show that Asrij and Arf1 physically interact. Further, we find that sophorolipids improve the solubility and monodispersibility of Asrij. Hence, we propose that sophorolipids could be novel additives for stabilization of membrane proteins. To our knowledge, this is the first study detailing methodology for the production and crystallization of a heterologously expressed scaffold membrane protein and will be widely applicable to understand membrane protein structure and function. Graphic
Keywords: Asrij/OCIAD1; Membrane protein crystallography; sophorolipids

Evolutionary conservation of protein dynamics: insights from all-atom molecular dynamics simulations of `peptidase' domain of Spt16 - Gaur, Neeraj K.; Ghosh, Biplab; Goyal, Venuka Durani; Kulkarni, Kiran; Makde, Ravindra D. (Journal of Biomolecular Structure and Dynamics, 2023)
Protein function is encoded in its sequence, manifested in its three-dimensional structure, and facilitated by its dynamics. Studies have suggested that protein structures with higher sequence similarity could have more similar patterns of dynamics. However, such studies of protein dynamics within and across protein families typically rely on coarse-grained models, or approximate metrics like crystallographic B-factors. This study uses mu s scale molecular dynamics (MD) simulations to explore the conservation of dynamics among homologs of similar to 50 kDa N-terminal module of Spt16 (Spt16N). Spt16N from Saccharomyces cerevisiae (Sc-Spt16N) and three of its homologs with 30-40% sequence identities were available in the PDB. To make our data-set more comprehensive, the crystal structure of an additional homolog (62% sequence identity with Sc-Spt16N) was solved at 1.7 angstrom resolution. Cumulative MD simulations of 6 mu s were carried out on these Spt16N structures and on two additional protein structures with varying degrees of similarity to it. The simulations revealed that correlation in patterns of backbone fluctuations vary linearly with sequence identity. This trend could not be inferred using crystallographic B-factors. Further, normal mode analysis suggested a similar pattern of inter-domain (inter-lobe) motions not only among Spt16N homologs, but also in the M24 peptidase structure. On the other hand, MD simulation results highlighted conserved motions that were found unique for Spt16N protein, this along with electrostatics trends shed light on functional aspects of Spt16N. Communicated by Ramaswamy H. Sarma.
Keywords: Backbone fluctuations; FACT complex; histone binding; interdomain motion; M24 peptidase